Is it really necessary to distinguish between error and fraud? A conceptual reflection inspired by researcher-practitioner experience in social security - SOUSSAN , Chifae (Revue Internationale des Sciences de Gestion, 2026)
Error and fraud lie at the heart of operational risk in social security. Both phenomena lead to financial losses, administrative inefficiencies and an erosion of public trust. Traditionally, the distinction between error and fraud is based on intent: error is unintentional, whereas fraud is deliberate. However, this distinction is difficult to establish in practice. Drawing on the researcher-actor’s experience and the existing literature, this article offers a theoretical reflection on the relevance of this distinction outside a punitive framework. The control mechanisms used to prevent, detect and correct errors and fraud are largely similar: audits, data analysis, automated controls and organisational arrangements. Thus, an integrated approach appears more relevant from a managerial perspective, focusing on processes rather than individual intentions. The study therefore proposes moving beyond the traditional dichotomy by considering fraud as a specific form of error. It highlights the importance of strengthening control systems, improving processes and promoting an ethical organisational culture in order to limit such malfunctions.